Influence of adhesives usage in complete dentures during adaptation period varying the degree of resorption of mandibular ridges - Silva, Marcela Dantas Dias da [UNESP]; Viotto, Hamile Emanuella do Carmo [UNESP]; Policastro, Vivian B. [UNESP]; Leite, Andressa Rosa Perin [UNESP]; Cassiano, Ana Flávia B. [UNESP]; Mendoza Marin, Danny Omar; Santana, Thaís de Sousa [UNESP]; Mollo, Francisco de Assis [UNESP]; Pero, Ana Carolina [UNESP] (Japan Prosthodontic Society, 2019)
Purpose: This study evaluated the effect of the use of a powder-type adhesive on masticatory performance and oral health related quality of life (OHRQoL) in patients with normal and resorbed mandibular ridges during adaptation period with complete dentures. Methods: Forty-two edentulous subjects (12 men, 30 women) were distributed in four groups: normal mandibular ridges with adhesive, n = 10; normal mandibular ridges without adhesive, n = 10; resorbed mandibular ridges with adhesive, n = 11; resorbed mandibular ridges without adhesive, n = 11. Masticatory performance was evaluated by sieving method and OHRQoL by Oral Health Impact Profile in Edentulous Adults (OHIP-EDENT) inventory at 30, 60 and 90 days after the insertion of new complete dentures. Data were analyzed using 2-way ANOVA test and Generalized Estimating Equations (GEEs), α = 0.05. Results: The use of adhesive resulted in better masticatory performance at 30 (35.76 ± 12.63%) and 60 days (30.06 ± 10.54%) after the insertion of the dentures and did not influence on OHRQoL in participants with normal ridges during the adaptation period. The use of adhesive did not interfere on masticatory performance during adaptation period and had a negative effect on masticatory discomfort/disability subscale OHRQoL at 30-day period [5.2(3.6, 6.8)] for resorbed mandibular ridges with new complete dentures. Conclusions: The use of adhesive can improve masticatory performance of new complete dentures users with normal mandibular ridges in the initial adaptation period up to 60 days after insertion. For resorbed ridges subjects, the use of adhesive had a negative impact on masticatory discomfort/disability OHRQoL at 30 days after insertion.
Keywords: Adhesives; Complete denture; Mastication; Physiological adaptation; Quality of life